2010
DOI: 10.1074/jbc.m110.171355
|View full text |Cite
|
Sign up to set email alerts
|

Substoichiometric Levels of Cu2+ Ions Accelerate the Kinetics of Fiber Formation and Promote Cell Toxicity of Amyloid-β from Alzheimer Disease

Abstract: A role for Cu 2؉ ions in Alzheimer disease is often disputed, as it is believed that Cu 2؉ ions only promote nontoxic amorphous aggregates of amyloid-␤ (A␤). In contrast with currently held opinion, we show that the presence of substoichiometric levels of Cu 2؉ ions in fact doubles the rate of production of amyloid fibers, accelerating both the nucleation and elongation of fiber formation. We suggest that binding of Cu 2؉ ions at a physiological pH causes A␤ to approach its isoelectric point, thus inducing sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
219
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 184 publications
(235 citation statements)
references
References 66 publications
13
219
3
Order By: Relevance
“…Thus, compounds that can modulate or shift the equilibrium of the A␤-Cu(II) complex to a less stable conformation or toward a non-toxic aggregated state could be a new therapeutic strategy for treating AD. Here it should be mentioned that a recent study showed, contrary to the previous reports, that it is the substoichiometric Cu(II) concentrations that are most cytotoxic, whereas an equimolar Cu(II) concentration does not increase A␤ cytotoxicity, and supra-stoichiometric Cu(II) concentrations reduce cytotoxicity (24).…”
Section: Aβ Monomercontrasting
confidence: 47%
See 1 more Smart Citation
“…Thus, compounds that can modulate or shift the equilibrium of the A␤-Cu(II) complex to a less stable conformation or toward a non-toxic aggregated state could be a new therapeutic strategy for treating AD. Here it should be mentioned that a recent study showed, contrary to the previous reports, that it is the substoichiometric Cu(II) concentrations that are most cytotoxic, whereas an equimolar Cu(II) concentration does not increase A␤ cytotoxicity, and supra-stoichiometric Cu(II) concentrations reduce cytotoxicity (24).…”
Section: Aβ Monomercontrasting
confidence: 47%
“…In all events elucidating the underlying molecular mechanisms of the A␤-Cu, interactions are vital for understanding the role of Cu(II) in the pathology of AD, and hence in developing new therapeutic strategies for the treatment of AD (7,22). Despite extensive studies, however, these mechanisms remain largely unsettled and conflicting effects have been reported; in some studies Cu(II) appears to be involved in amyloid oligomerization (4,23,24), other studies report that Cu(II) does enhance aggregation but only along non-amyloidogenic pathways (17,25), or even that Cu(II) inhibits the aggregation of A␤ (26). We recently showed that Cu(II) could induce both oligomerization and non-oligomerization pathways of A␤ on the millisecond-second time scale (27).…”
mentioning
confidence: 99%
“…A␤ forms fibers much faster than A␤ and is also more toxic in vivo (61)(62)(63)(64). The heightened rate of fiber nucleation and elongation observed for A␤ (11-40/42) may be caused by the loss of negatively charged side chains, as it is known that the pI and charge of A␤ have a profound influence on its rate of fiber formation (22,65). The absence of a number of charged residues at the N terminus increases the theoretical pI from 5.1 for A␤ (1-40/42) to 6.0 for A␤ (11-40/42) .…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is also responsible for the transport of the labile pool of Cu 2ϩ ions in blood plasma (21). Of note, the A␤-Cu 2ϩ interaction and its role in AD have received significant interest (22)(23)(24), and Cu 2ϩ may be transferred from A␤ to HSA (25), meaning that albumin could have two mechanisms by which it inhibits fiber formation.…”
Section: Discussionmentioning
confidence: 99%